Evaluation of psychological stress and cortisol levels in males with and without gingivitis - Aral, Kubra; R Milward, Michael; R Cooper, Paul; Celik Guler, Ozge (Annals of Medical Research, 2021)
Aim: Gingivitis is a prevalent health problem seen most commonly in males. Psychological stress is also associated with periodontal disease. Thus, to evaluate the possible role of stress in gingivitis, this study investigated the psychological stress and cortisol levels in males with and without gingivitis. Material and Methods: Sixty systemically healthy males between 18 and 28 years were divided into two groups, including those with generalized gingivitis (G) (n=30) and periodontally healthy controls (H) (n=30). Gingival crevicular fluid (GCF) and saliva samples were obtained for determination of cortisol levels using enzyme-linked immunosorbent assay. Plaque (PI) and gingival index (GI), bleeding on probing (BOP), probing depth (PD) and clinical attachment level (CAL) were noted. In addition, BECK depression inventory (BDI), Perceived Stress Scale (PSS), and Oral Health Impact Profile-14 (OHIP-14) were recorded from all participants. Results: PI, GI, BOP (p0.01), and PD (p0.05). Cortisol levels in saliva and GCF were similar between groups (p>0.05). Conclusion: Psychological stress and cortisol levels in GCF and saliva were found to be similar in males with and without gingivitis.